2022
DOI: 10.1155/2022/1565038
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Superior Semicircular Canal Morphology and Its Relationship with Glenoid Fossa Roof Thickness Using Cone Beam Computed Tomography

Abstract: Purpose. This study aimed to evaluate the bone thickness of the superior semicircular canal (SSC) roof and its relationship with the roof thickness of the glenoid fossa (RGF). Methods. The cone beam computed tomography (CBCT) images of 280 patients (560 temporal regions) were surveyed. The lowest thickness of the SSC roof was measured and categorized based on the radiological patterns of the Cisneros et al. classification. The thickness of GF and the presence of dehiscence in this part were determined, as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…More specifically, a 2012 review of 582 ears found that the association between aging and osteopenia of the SSC roof is especially pronounced among menopausal women, as women over 45 years old were found to have thinner SSC roof compared to women under 45 years old, but men over 45 years old were found to have similar SSC roof thickness compared to men under 45 years old 11 . Most recently, a 2022 investigation found females over 45 years old to be 3.79 times more likely to have radiographic SCD than females under 45 years old, but such finding did not apply to males 12 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…More specifically, a 2012 review of 582 ears found that the association between aging and osteopenia of the SSC roof is especially pronounced among menopausal women, as women over 45 years old were found to have thinner SSC roof compared to women under 45 years old, but men over 45 years old were found to have similar SSC roof thickness compared to men under 45 years old 11 . Most recently, a 2022 investigation found females over 45 years old to be 3.79 times more likely to have radiographic SCD than females under 45 years old, but such finding did not apply to males 12 …”
Section: Discussionmentioning
confidence: 99%
“…11 Most recently, a 2022 investigation found females over 45 years old to be 3.79 times more likely to have radiographic SCD than females under 45 years old, but such finding did not apply to males. 12 Older women are at higher risk for osteoporosis due to reduced estrogen levels. 27 Given the association of older age and female sex with thinning of the SCD roof, researchers have hypothesized that osteoporosis/ osteopenia may be involved in the etiology of acquired SCD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations